SELF-ASSESSMENT ON PATIENT SAFETY COMPETENCIES AMONG INTERNSHIP NURSING STUDENTS OF SELECTED COLLEGES, ODISHA - RAGHAVENDRAN, M. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Human errors are common in health care infrastructure. Most challenging error among the healthcare system is said to be medical error. As a part of nursing education, patient safety always makes its priority, globally. It is clear to explain that involvement of student nurses in patient safety and reduction of error will help in developing competence among the student nurses. The Self-Assessment on patient safety competencies among Internship Nursing students of selected colleges, Odisha was conducted with the objectives to assess the Self-Assessment level and to associate the Self-Assessment level regarding patient safety competencies among Internship Nursing students of selected colleges with their selected demographic variables. A quantitative evaluatory research approach with A Non - Experimental Survey research design was used with 170 Internship nursing students from selected colleges were selected as samples by Non- probability convenient sampling technique. The result of the study shows that out of 170 nursing students,32 (18.8%) has Low level, 62 (36.5%) have Moderately level and 76 (44.7%) have high level of patient safety competencies. the mean and standard deviation for self-assessment on patient safety competencies level of knowledge was 15.3 and 2.08, for skill it was 52.6 and 4.52, for attitude 2.6 and3.81 respectively. With regard to association, there is some significant association between the self-assessment on patient safety competencies level with the selected demographic variables like Gender and previous knowledge on patient safety among internship nursing students. The study concludes that most of internship students have high level in self assessment on patient safety competencies, the knowledge on patient safety has shows some significance